Kajian Erosi Dan Hasil Sedimen Untuk Konservasi Lahan DAS Kreo Hulu - Zulfa Fauzi, Rifky Muhammad; Maryono, Maryono (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Watershed as rainwater catchment are is susceptible with erosion and sedimentaion problems. The calculation of erosion and sediment yield can be calculated with USLE and SDR (Sediment Delivery Ratio) method at each area unit. This research intends to find out the erosion value, distribution and prediction of sediment yield contained in Kreo Hulu Watershed in 2009-2014. Data accumulation methods for the research are observation, documentation, and field measurement. The erosion forecast result in this research obtained based on overlay few maps, that is rain erosivity map, soil erodibility map, length of slope map, management and conservation soil map. This research was construct with using rainfall data from 2009 until 2014. Based on the calculations model of erosion is known that the erosion in the watershed upstream Kreo fluctuation occurring annually. With the result of erosion from 2009 until 2014 are respectively 17.45 tons; 18.78 tons; 17.83 tons; 25.70 tons; 31.62 tons; 26.17 tons. Sediment yield estimates obtained by the relationship between the unit value erosion (based mapping unit), as well as the erosion area of the unit value of Sediment Delivery Ratio in watershed. By calculation of these factors, the value of watershed sediment Kreo Hulu forecast results for 2009-2014 are respectively 2,78 tons, 2.93 tons; 2,78 tons; 4.01 tons; 4.93 tons; 4,08 tons. Spatial distribution of erosion prediction Kreo upstream watershed of very high value erosion is largely rural area/village Gunungpati, Banjarejo, Karangmalang, Lebak and Cepoko. Weight and middle erosion are covering parts of Pasigitan, Branjang, Kalisidi, and Tinjomoyo. Then need to increase conservation of alternative methods land mechanically and vegetative at upstream Kreo watershed.